A57: Four Prolonged Cases of Eosinophilic Fasciitis in Children. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Hui‐Yuen, Joyce S; Lauren, Christine; Garzon, Maria; Starr, Amy J.; Imundo, Lisa F.
Abstract : Background/Purpose: Eosinophilic fasciitis (EF) is a rare connective tissue disease characterized by a progressive inflammatory thickening of skin and soft tissues. Diagnosis is often based on characteristic clinical and biopsy findings, and treatment remains challenging. Pediatric data describing clinical course and treatment recommendations remain scarce. Methods: This is a case series of all patients diagnosed with EF at our institution in the last 8 years. A retrospective chart review was conducted and data collected on clinical signs and symptoms and laboratory data at diagnosis, disease course, and treatment outcomes. Descriptive statistics were used when appropriate. Results: We describe four pediatric patients with EF, with a mean follow‐up of 54 months. Three of the four patients had preceding diagnoses before beginning treatment for EF. All patients had peripheral eosinophilia at diagnosis, two had positive anti‐thyroid antibodies, and two had high levels of total cholesterol. Treatment induction in all patients consisted of intravenous methylprednisone (30mg/kg/day to a maximum of 1g daily for 3 days). All patients required at least one steroid‐sparing agent (methotrexate at 15mg/m 2 /dose and/or mycophenolate mofetil (MMF) at 600mg/m 2 /dose) for disease maintenance post‐induction. The mean length of treatment with methotrexate was 23 months, discontinued in only one patient. The mean length of treatment with MMF was 8.3 months. All patients had improvement in skin findings, and all abnormal laboratory findings normalized after treatment with intravenous corticosteroid. One patient had a disease flare less than 12 months after being weaned off cortico‐steroids and methotrexate. Another patient developed a second autoimmune disease five years after treatment for EF. All patients had residual skin changes, and 3 patients had signs of lipodystrophy and/or subcutaneous fat atrophy after treatment. Conclusion: EF is often difficult to diagnose and has a variable course in children. We report four cases of prolonged EF, the only four EF patients diagnosed in our practice. Our data suggest a more severe course at earlier age of onset, with higher likelihood of recurrence. Our data also confirm the efficacy of corticosteroid treatment as first‐line therapy, and suggest a role for methotrexate as a promising steroid‐sparing agent. This is the first case series to describe successful treatment of EF with the addition of mycophenolate mofetil to a treatment course of methotrexate and corticosteroid therapy. Three of our four patients required triple therapy for disease control, which may be suggestive of a more severe disease course in the pediatric population.